Penyelesaian Capacitated Closed Vehicle Routing Problem With Time Windows Menggunakan Biased Random Key Genetic Algorithm dengan PopulasiTerdegradasi (BRKGA-PD) - Christiana, Listy Avri, Hari Prasetyo, ST, MT, Ph.D (2016)
This research presents a Biased Random Key Genetic Algorithm with degraded population (BRKGA-PD) to address the Capacitated Closed Vehicle Routing Problem with Time Windows (CCVRPTW) in distributing soft drink. The objective is to determine some closed routes to meet the consumer demand incorporating the time constraint and the capacity constraint of the vehicle used so that the total cost of distribution is minimum. The proposed algorithm adopted an incremental extinction of the population, i.e. the size of population decreases gradually along with iterations on the process of forming the new generation. BRKGA-PD is encoded using the Matlab programming language while the best parameter setting is obtained through extensive numerical tests. The obtained solution of the BRKGA-PD is sub routes with minimum distribution cost. The performance of the algorithm is compared with two other methods, the standard BRKGA and a heuristic. From this research, it is concluded that: (1) in terms of the total distribution cost, the BRKGA-PD is able to improve the standard BRKGA and (2) the BRKGA-PD also outperforms the heuristic method, as it can save the cost by Rp. 92,662.00.